A GRADIENT-LESS PARAMETER APPROACH FOR SHAPE OPTIMIZATION - TIAN Shuai; ZHANG Qing; QIN XianRong; SUN YuanTao (Jixie qiangdu)
A gradient-less parametrical approach has been employed to optimize the stress concentration on local part. The design boundary was represented by splines and the shape of boundary can be varied by adjusting the coordinate of control points.By doing so to varying the stress distribution on design boundary. The average stress on design boundary was selected as the reference stress. Control points with higher stress than average stress move outward to add material; meanwhile,control points with lower stress move inward to reduce material to fulfill the shape optimization. Two feasible zones and three start shapes have been employed in optimization instances to compare the influence of the different feasible zones and start shapes,respectively.The influence of the control parameters to the optimization process and result have also been studied.